2011
DOI: 10.1007/s00280-011-1786-6
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II study of gemcitabine as a fixed dose rate infusion and S-1 combination therapy (FGS) in gemcitabine-refractory pancreatic cancer patients

Abstract: This combination regimen of FGS is active and well tolerated in patients with Gem-refractory PC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…There was no standard second-line therapy after first-line chemotherapy failure. A recent phase I/II study showed that combination therapy of fixed dose rate infusion of GEM with S-1 (FGS) provided a promising antitumor activity and tolerable toxicity in GEM-refractory metastatic PC patients [24]. The median OS and PFS were 7.0 and 2.8 months respectively, seemed to be better than those treated with S-1 monotherapy [25,26].…”
Section: Discussionmentioning
confidence: 97%
“…There was no standard second-line therapy after first-line chemotherapy failure. A recent phase I/II study showed that combination therapy of fixed dose rate infusion of GEM with S-1 (FGS) provided a promising antitumor activity and tolerable toxicity in GEM-refractory metastatic PC patients [24]. The median OS and PFS were 7.0 and 2.8 months respectively, seemed to be better than those treated with S-1 monotherapy [25,26].…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, another phase II RCT showed no significant difference in OS between a group receiving selumetinib (5.4 months) and one receiving capecitabine (5.0 months)25. Other regimens, such as S-1 plus radiotherapy, S-1 with a fixed dose of gemcitabine, and paclitaxel plus S-1 have been used for pancreatic cancer following gemcitabine failure262728, but RCTs have not been conducted for further verification.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studies have identified that S-1 achieve favorable therapeutic effect in GEM-resistant PC. 27 , 28 Thus, treatment comparison between GEM and GS had been launched in several large-scale clinical trials.…”
Section: Discussionmentioning
confidence: 99%